Behavioral and Neurochemical Deficits in Aging Rats with Increased Neonatal Iron Intake: Silibinin’s Neuroprotection by Maintaining Redox Balance - Chen, Hanqing; Wang, Xijin; Wang, Meihua; Yang, Liu; Yan, Zhiqiang; Zhang, Yuhong; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2015)
Aging is a critical risk factor for Parkinson’s disease. Silibinin, a major flavonoid in Silybum marianum, has been suggested to display neuroprotective properties against various neurodegenerative diseases. In the present study, we observed that neonatal iron (120 μg/g body weight) supplementation resulted in significant abnormality of behavior and depletion of striatal dopamine in the aging male and female rats while it did not do so in the young male and female rats. No significant change in striatal serotonin content was observed in the aging male and female rats with neonatal supplementation of the same dose of iron. Furthermore, we found that the neonatal iron supplementation resulted in significant increase in malondialdehyde (MDA) and decrease in glutathione (GSH) in the substantia nigra (SN) of the aging male and female rats. No significant change in content of MDA and GSH was observed in the cerebellum of the aging male and female rats with the neonatal iron supplementation. Interestingly, silibinin (25 and 50 mg/kg body weight) treatment significantly and dose-dependently attenuated depletion of striatal dopamine and improved abnormality of behavior in the aging male and female rats with the neonatal iron supplementation. Moreover, silibinin significantly reduced MDA content and increased GSH content in the SN of the aging male and female rats. Taken together, our results indicate that elevated neonatal iron supplementation may result in neurochemical and behavioral deficits in the male and female rats with aging and silibinin may exert dopaminergic neuroprotection by maintaining redox balance.